Public Trust in Dentists among Arabic Populations - Aceil Al-Khatib; Radwan Abed Alhaleem; Rama Qaffaf (International Journal of Dentistry)
Objective. To investigate public trust in dentists, fear of dentists, factors related to trust, and the impact of the COVID-19 pandemic on the trust in dentists. Materials and Methods. We used an Arabic online anonymous survey to collect data from a random population of 838 adults to investigate public trust in dentists, the factors they perceive to affect trust, their perception of key factors in the dentist-patient relationship, fear of dentists, and the impact of the COVID-19 pandemic on the level of their trust in the dentists. Results. Eight hundred thirty-eight subjects with a mean age of 28.5 responded to the survey (595 (71%) females, 235 (28%) males, and 8 (1%) did not specify their gender). More than half trust their dentist. The COVID-19 pandemic did not decrease trust in dentists according to 62.2%. There were significant gender differences in reporting fear of dentists (p<0.001) and in the perception of factors affecting trust (p=0.028). Honesty was chosen by 583 (69.6%), competence by 549 (65.5), and dentist’s reputation by 443 (52.9%). Conclusions. The findings of this study show that the majority of the public trust dentists, more females reported fear of dentists, and the majority perceived honesty, competence, and reputation as key factors affecting trust in the dentist-patient relationship. The majority reported that the COVID-19 pandemic did not have a negative impact on their trust in dentists.